Stereotypes of Past-Slavery and "Stereo-styles" in Post-Slavery: A Multidimensional, Interactionist Perspective on Contemporary Hierarchies - Pelckmans, Lotte (The International journal of African historical studies, 2015)
[...]in addition to the anachronism and polysemy inherent in discursive categories and legal pluralism, we can observe a normative pluralism (see Eric Hahonou in this volume), which is expressed in actual behavioral practice and normative claims. [...]the prefix (stereo) reminds us that it is crucial to adopt relational research methods.